Effective Feature Extraction Method in Novel Key Generation Using QR Code to secure the data - Sandha, Sandha; Durga, M. Ganaga (International Journal of Computer Sciences and Engineering, 2025)
In cloud environment data can be stored and shared between other resources. Any symmetric or asymmetric algorithm is used for secure data in cloud. We need to store the keys in database .The main objective of our work is to improve the protection by encrypting the information with the key generated by QR. It proposes a novel algorithm for generating key using QR image features. It is a reliable and flexible method of key generation for information security. Existing technique for key generation using feature extraction have problem such as high extraction time and high searching time .Existing method need to store more images and stored image may be damaged,. In cloud environment, searching process for authentication causes high network bandwidth, congestion and delay. This paper suggests QR code, a two dimensional code can be used for authentication. Key is extracted from the user unique QR code which is used to achieve the fast retrieval of data from the server. Lost image can be recovered using QR error correction technique. Particularly it is very useful to access mobile applications and there is no need to store more images in server. Additionally extracted key is used as prime factors p and q of the modulus n in RSA for encryption process which tries to secure from mathematical attack. This novel key is applied with asymmetric algorithm.